The Production system of International Packaging, Inc. - Custodio, Yolanda; Del Castillo, Ruth; Deligente, Ethel; Guillermo, Antoinette; Padilla, Timoteo (College of Engineering, 1984)
Having recognized that any organization can and must be treated as a system, we might also take cognizance of the fact that the operations activity itself is a subsystem, that is, a system within a system. To say that production is a system is to say that the operations activity consists of a number of interrelated elements. Some of these are performed in sequence, while others are carried out concurrently. The important thing, however, is that the manner in which one element of the operations activity is conducted will most likely have an effect on one or more of the other elements.This becomes evident when we consider what is involved in the management of a firm's operations. The operations personnel in any organization can be said to have four basic responsibilities. These are to produce the firm's products or services in a way such that (1) quantity requirements will be satisfied, (2) established delivery or completion dates will be met, and (4) the most economical methods for accomplishing the foregoing will have been selected an applied. Quantity requirements and established completion dates will, of course, reflect the demands of the consumers of the firm's products or services. To satisfy these, operating personnel, as a rule, will be compelled to plan the production activity prior to the point at which the demands actually occur. This is true for a number of reasons. First, unless the required factors of production are on hand at the time an order for a given quantity is receive, it is unlikely that the delivery date desired by the customer can be met, because the time required to produce manpower, materials, equipment, and buildings usually far exceeds what is generally accepted as being a reasonable delivery time. And second, even ig this were not the case, the firm that would procure and utilize factors of production only at the time at which they are required to satisfy customer orders would, more often than not, find that it would be producing and purchasing in uneconomic lot sizes and experiencing wide fluctuations in the output capacity required at any single moment; this would serve to generate excessive costs. For these reasons, every concern engages in production planning. This involves forecasting the demand for the firm's products and services and translating this forecast into its equivalent demand for various factors of production. These resultant factor-of-production demand schedules might be adjusted to eliminate wide fluctuations or to permit producing and purchasing in economic lot sizes. In their final form, however, they provide the operations manager with information on the kind and amount of materials, manpower, and production facilities which will be required at various future points in time. Arrangements can then be made to procure these factors of production prior to the times at which they will actually be needed. Doing so facilitates the production department's being able to meet delivery dates on orders it subsequently receives. However, even if the needed factors of production are on hand at the time actual orders are received, quantity requirement and stipulated delivery dates can be satisfied only if steps are taken to utilize these factors in an efficient manner. This calls for scheduling the required work. providing operating departments with necessary instructions, checking on production progress and inaugurating corrective action when such action is needed. All this is called "Production Control." And finally, we have noted that operating personnel are expected to produce the organization's products and services not only in the required quantities, at the required times, and with the required quality, but also in the most economical manner. As a consequence, methods analyses must be made of the alternative ways in which the firm's goods and services can be produced with a view toward determining the most efficient of the alternative work methods. Also, a need is created for materials handling analyses and for plant and office layout analyses whose purpose is to develop a handling system and an arrangement of departments and work stations which will serve to minimize the cost to be associated with the movement of personnel and materials from one location to another.